The issues and advantages of the use of new technology in Saudi education: A literature review - Alharbi, Omran; Alshammari, Yousef; Aldosari, Mohammed Owais; Albazie, Haifa Abdullah (Advances in Social Sciences Research Journal, 2019)
Fast developments in technology have led to an increasingly widespread use of smartphone and tablet computing technologies. Schools and organizations around the world are struggling to keep pace with the growth of technology through the adoption of new technologies such as Google Education Tools. Saudi Arabian schools are no exception. Recently, several universities and schools in the Kingdom of Saudi Arabia (KSA) have started to employ new technologies such as Google Classroom in their teaching and learning process, in order to make education available to their students without temporal or spatial restrictions. On the other hand, there has been little discussion about the benefits and problems of using such technologies in KSA schools. Therefore, this paper is an attempt to determine benefits and problems of the latest technologies that have been adopted in KSA schools. It makes recommendations on how new technology can be more effectively used in the classroom, as well as discussing its potential advantages and pitfalls.